PRAKTEK PENGGUNAAN SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN DALAM RANGKAIAN PROSES PENJAMINAN ATAS KREDIT DI KABUPATEN SLEMAN DIY - , ISHAK ISMAIL DAMANIK ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Mortgage Procuration Letter is a kind of the procuration letters which are given by guarantor to other party (it is usually given by bank for charging the mortgage) by signing the Mortgage Granting Deed. In principle, the Mortgage Procuration Letter is made because the Mortgage Granting Deed cannot be made or signed for certain reasons yet. The main function of the Mortgage Procuration Letter to guarantee that in the future that it determined the relevant bank or creditor can represent a guarantor or charge the mortage. The Mortgage Procuration Letter is regulated in Article 15, Law No. 4/1996 on the Mortgage Procuration Letter. This study was conducted with population of 30 Mortage Procuration Letters which collected from three public notaries of Land Deed Officials based in District of Sleman. All 30 Mortgage Procuration Letters were made as samples of the study. The results of the study indicate that the use of Mortgage Procuration Letters were in accordance with the prevailing legislations. The use of Mortgage Procuration Letters in loan agreement consisted of three steps, i.e., before the use of the Mortgage Procuration Letters, the making of credit agreement, and the giving of the Mortgage Procuration Letters. The use of Mortgage Procuration Letters was constrained during the binding process to be the Mortgage Granting Deeds and the registration of the Mortgage Granting Deed. Two factors were identified as the constraints in the use of Mortgage Procuration Letters as the Mortgage Granting Deed, i.e. expensive costs and short period of time. To overcome such constraints, efforts should be done to renew any expired Mortgage Procuration Letters in accordance with the prevailing legislations and to follow up to be the Mortgage Granting Deeds.